USO DO ENERGYPLUS EM PESQUISAS BRASILEIRAS - Santos, Ana Carolina dos; Lima, João Victor de Souza; Faria, João Roberto Gomes de; Fontes, Maria Solange Gurgel de Castro (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
Thermal and energetic performance of buildings are important issues on scientific and technological research of the built environment. Simulation software is a very common tool in these studies, both in the search for new knowledge and for aiding decision-making. The aim of this study was to investigate the scientific applicability of one of these tools, EnergyPlus, evidencing questions about its usability, applicability and operation. An exploratory methodological approach involved the systematic review of the full papers in the ENTAC proceedings and a subsequent bibliometric analysis. The results show a trend of increasing use of that software in scientific experiments in recent years, mainly with an inductive approach. Currently its predominant utilization is evaluation of bioclimatic strategies, construction systems and prescriptive methods. It was also observed that the level of complexity of the research has increased over the years, and studies directed to aid the software operation have intensified, which demonstrates more familiarity of the researchers with the tool.